2001
DOI: 10.1902/jop.2001.72.5.696
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of a New Compact Computed Tomography System for Evaluating the Outcome of Regenerative Therapy: A Case Report

Abstract: We consider that CT is a useful aid in periodontal examination and diagnosis, and in the prediction and evaluation of periodontal treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…58,59 Periodontics The first reported applications of CBCT in periodontology were for diagnostic and treatment-outcome evaluations of periodontitis. 60 Ex vivo studies later characterized the ability of CBCT to accurately reconstruct periodontal intrabony and fenestration defects, dehiscences, and root furcation involvements in comparison with radiography, MDCT, and histologic measurements. [61][62][63][64][65] CBCT 3D geometric accuracy has been suggested to be equal to radiography and MDCT but with better observer-rated image quality than MDCT as well as superior periodontal-defect detection than radiography.…”
Section: Endodonticsmentioning
confidence: 99%
“…58,59 Periodontics The first reported applications of CBCT in periodontology were for diagnostic and treatment-outcome evaluations of periodontitis. 60 Ex vivo studies later characterized the ability of CBCT to accurately reconstruct periodontal intrabony and fenestration defects, dehiscences, and root furcation involvements in comparison with radiography, MDCT, and histologic measurements. [61][62][63][64][65] CBCT 3D geometric accuracy has been suggested to be equal to radiography and MDCT but with better observer-rated image quality than MDCT as well as superior periodontal-defect detection than radiography.…”
Section: Endodonticsmentioning
confidence: 99%
“…These results were supported in a recent study in a clinical situation (Grimard et al 2009). A case report showed that regeneration of bone in a furcal defect could be more accurately monitored using CBCT compared to IR (Ito et al 2001b). …”
Section: Cone Beam Computed Tomography and Periodonticsmentioning
confidence: 99%
“…The system is characterized by a high resolution (voxel size, 0.125 mm), quick operation (exposure time, 17 s), and a low effective dose (about 10 mSv/exposure.). [6][7][8][9][10][11] We report herein a newly developed m CT system that employs the method used for limited cone-beam CT in dentistry. Figure 1 shows an overview of the new m CT system.…”
Section: Introductionmentioning
confidence: 99%